Obtenção de emulsões asfálticas convencionais e modificadas com argilas e nanoargilas - Torres, Júlia Cristina de Lima (2013)
The increasing demand for asphalt leads to the development of techniques that can improve the quality of products and increase the useful working life of pavements. Consequently, there is a growing application of asphalt emulsions, which are produced from a mixture of petroleum asphalt cement (CAP) with an aqueous phase. The main advantage of asphalt emulsions is its cold application, reducing energy costs. Conventional emulsions are obtained using asphalt, water, solvent, and additives. The modified asphalt emulsion is developed by adding a modifying agent to conventional emulsions. These modifiers can be natural fibers, waste polymers, nanomaterials. In this work modified asphalt emulsion were obtained using organoclays. First, it was prepared a conventional asphalt emulsion with the following mass proportion: 50% of 50/70 penetration grade CAP, 0.6% of additives and 3% of emulsifier, 20% of solvent and 26.4% of water. It was used bentonite and vermiculite (1% and 4%) to obtain the modified asphalt emulsion. Bentonite and vermiculite were added in its raw state and as an organoclay form and as an organoclay-acid form, resulting in 26 experimental runs. The methodology described by Qian et al. (2011), with modifications, was used to obtain the organoclay and the organoclay-acid form. infrared spectroscopy (IR)) were used to characterize the clays and nanoclays. The emulsions were prepared in a colloidal mill, using 30 minutes and 1 hour as mixing time. After, the emulsions were characterized. The following tests were performed, in accordance with the Brazilian specifications (DNER- 369/97): sieve analysis, Saybolt Furol viscosity, pH determination, density, settlement and storage stability, residue by evaporation, and penetration of residue. Finally, it can be concluded that the use of nanoclays as asphalt modifiers represent a viable alternative to the road paving industry